Oscillation of solutions for a class of nonlinear fractional difference equations - Secer, Aydin; Adiguzel, Hakan (INT SCIENTIFIC RESEARCH PUBLICATIONS, 2016)
In this paper, we investigate the oscillation of the following nonlinear fractional difference equations, Delta (a (t) [Delta (r (t) (Delta(alpha)x(t))gamma 1)]gamma 2) + q(t) f (Sigma(t-1+alpha)(s=t0) (t - s - 1)((-alpha)) x(s)) = 0, where t is an element of Nt0+1-alpha, gamma(1) and gamma(2) are the quotient of two odd positive number, and Delta(alpha) denotes the Riemann-Liouville fractional difference operator of order 0 < a <= 1. (C) 2016 All rights reserved.
Keywords: Fractional order; fractional difference equation; oscillation; nonlinear; difference equations; oscillatory solutions; EXISTENCE; STABILITY; Mathematics